Energetic studies of urea derivatives: Standard molar enthalpy of formation of 3,4,4 '-trichlorocarbanilide - Maria D M C R Ribeiro da Silva (2010)
Thermochemical and thermophysical studies have been carried out for crystalline 3,4,4'-trichlorocarbanilide. The standard (p degrees = 0.1 MPa) molar enthalpy of formation, at T = 298.15 K, for the crystalline 3,4,4'-trichlorocarbanilide (TCC) was experimentally determined using rotating-bomb combustion calorimetry, as -(234.6 +/- 8.3) kJ . mol(-1). The standard enthalpy of sublimation, at the reference temperature of 298.15 K, was measured by the vacuum drop microcalorimetric technique, using a High Temperature Calvet Microcalorimeter as (182.1 +/- 1.7) kJ . mol(-1). These two thermochemical parameters yielded the standard molar enthalpy of formation of the studied compound, in the gaseous phase, at T = 298.15 K, as -(52.5 +/- 8.5) kJ . mol(-1). This parameter was also calculated by computational thermochemistry at M05-2X/6-311++G and B3LYP/6-311++G(3df, 2p) levels, with a deviation less than 4.5 kJ . mol(-1) from experimental value. Moreover, the thermophysical study was made by differential scanning calorimetry. DSC, over the temperature interval between T = 263K and its onset fusion temperature, T = (527.5 +/- 0.4) K. A solid-solid phase transition was found at T = (428 +/- 1) K, with the enthalpy of transition of (6.1 +/- 0.1) kJ . mol(-1). The X-ray crystal structure of TCC was determined and the three-centred N-H center dot center dot center dot O=C hydrogen bonds present analyzed.